Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Terhadap Kinerja Pegawai Pada Badan Pengelolaa Keuangan dan Pendapatan Daerah Kabupaten Pamekasan Yang Di Mediasi Oleh Motivasi - Sri Mulyani; Nugroho Mardi; Agus Setiawan (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This article reviews the Influence of Leadership Style, Work Environment, on Employee Performance with Motivation as an Intervening Variable. Where the influence of employee performance on motivation as a mediating variable includes leadership style, work environment, so in this article the author will review two variables that have a role or influence on employee performance with motivation as a mediating variable. The implementation of this literature review article is as follows: 1) leadership style influences employee performance; 2) leadership style influences motivation; 3) work environment affects motivation; 4) work environment influences employee performance; 5) motivation influences employee performance; 6) leadership style not influence employee performance mediated motivation; 7) work environment not influence employee performance mediated motivation.